2012
DOI: 10.1007/s13593-012-0099-4
|View full text |Cite
|
Sign up to set email alerts
|

No-till and cover crops shift soil microbial abundance and diversity in Laos tropical grasslands

Abstract: Agricultural practices affect the physical and chemical characteristics of the soil, which in turn may influence soil microorganisms with consequences on soil biological functioning. However, there is little knowledge on the interactions between agricultural management, soil physicochemical properties, and soil microbial communities, notably in tropical ecosystems with few studies conducted in strongly weathered and acid soils. Here, we investigated the early effect of tillage and crop residues management on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 31 publications
8
54
1
5
Order By: Relevance
“…6). Additional research is needed to analyze the cumulative effects of a mixture of cover/relay crops under NT on root exudation, and changes in rhizospheric biological activities, which influence nutrients and C cycling by improving soil aggregation and physically protecting plant-derived SOC and microbially derived organic C. In an acid tropical grassland environment in Laos, Lienhard et al (2013) showed that high and diversified biomass-C inputs under NT induced significant modifications when compared with conventional plow-based tillage. NT increased aggregate stability and soil organic carbon content, enhanced nutrient availability and microbial biomass as a result of a simultaneous increase of fungal and bacterial densities.…”
Section: Comparison Among Sub-tropical and Tropical Sitesmentioning
confidence: 99%
“…6). Additional research is needed to analyze the cumulative effects of a mixture of cover/relay crops under NT on root exudation, and changes in rhizospheric biological activities, which influence nutrients and C cycling by improving soil aggregation and physically protecting plant-derived SOC and microbially derived organic C. In an acid tropical grassland environment in Laos, Lienhard et al (2013) showed that high and diversified biomass-C inputs under NT induced significant modifications when compared with conventional plow-based tillage. NT increased aggregate stability and soil organic carbon content, enhanced nutrient availability and microbial biomass as a result of a simultaneous increase of fungal and bacterial densities.…”
Section: Comparison Among Sub-tropical and Tropical Sitesmentioning
confidence: 99%
“…It is based on three fundamental principles: 1. diversification of crop rotation, 2. reduction of soil tillage and 3. permanent soil cover (FAO, 2017). Compared to classical plough tillage, reduced tillage has several advantages, such as reduction of fuel costs, decreased disturbance for soil organisms, preservation of soil fertility, higher soil macroporosity, better water retention (Holland, 2004;Lienhard et al, 2013;Mazzoncini et al, 2011;Murugan et al, 2014;Palm et al, 2014;Sapkota et al, 2012;Soane et al, 2012). In contrast, detrimental effects, such as increased soil density, reduction of mineralisation or slowing of soil warming, could be observed in reduced tillage systems, especially with direct seeding (Soane et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Among all soil properties, microbial biomass and soil enzyme activities prove to be sensitive indicators of soil quality as they are measurements which rapidly respond to changes due to different management and environmental factors (Alvear et al, 2005). Soil perturbations, such as tillage, can alter microbial processes, biogeochemical nutrient cycles (overall C stored) (Janzen et al, 1997) thus modifying the structural and functional diversities of the soil microbial communities (Lienhard et al, 2012). In fact, physical disturbance exposes Soil organic matter (SOM) to biological activity, thus facilitating the penetration of water at greater depths and accelerating its decomposition.…”
Section: Introductionmentioning
confidence: 99%